Top Management's Communication and Employees' Commitment to Change: The Role of Perceived Procedural Fairness and Past Change Experience. (June 2021) - Faupel, Stefanie; Helpap, Sevda
Studies on the effects of communication strategies applied by top management during organizational change are scarce. While first research indicates that a participatory communication strategy is more effective in evoking employees' commitment to change than a programmatic change communication strategy, how this effect occurs remains unclear. The present study addresses this gap by investigating perceived procedural fairness as mediating and past change experience as moderating factor in the relationship between communication strategy and commitment to change. Results of the quasi-experimental study indicate that participatory change communication strengthens fairness perceptions more than programmatic change communication does. Results indicate that perceived procedural fairness explains the effect of change communication strategy on commitment to change. No moderating but a direct effect of past change experiences was found. Results show the potential of participatory change communication, and the importance of procedural fairness early in change, which are valuable insights for managers who initiate change.